The creation function of a junior listing venue: An empirical test on the Alternative Investment Market - Valerie Revest; Alessandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Stock markets perform a creation function if the inflow of financial capital in the birth of new privately-held firms is stimulated by the promise of stock market liquidity at a later point in time. Junior stock market segments, characterized by lighter listing procedures and costs, may be suited to perform a creation function, but their liquidity promise may not be reliable due information opacity. We test the creation function of the Alternative Investment Market (AIM), the junior segment of the London Stock Exchange (LSE), by means of dynamic panel data models, where entry at the sectoral level is regressed on capital raised at IPO on AIM and on the LSE main market, venture capital investments, and control variables. Our sample includes UK manufacturing sectors over the 2004-2012 time span. We find that sectors that raised more capital at IPO on AIM housed more new entrants in the subsequent years, whereas the results on main market IPOs and venture capital financing are mixed. The magnitude of this effect increases as the amounts of raised capital are aggregated over longer time horizons. Results are confirmed after endogeneity tests (pseudo diff-in-diff and 2-stage residual inclusion estimators).
Keywords: E44; G23; L26; L60; M13; 330; Entry; Firm creation; Stock exchange; Junior stock market